Homocyclic o-dicarboxaldehydes: Derivatization reagents for sensitive analysis of amino acids and related compounds by capillary and microchip electrophoresis - Celá, Andrea; Glatz, Zdeněk (Electrophoresis, 2020)
Amino acids are essential compounds for living organisms, and their determination in biological fluids is crucial for the clinical analysis and diagnosis of many diseases. However, the detection of most amino acids is hindered by the lack of a strong chromophore/fluorophore or electrochemically active group in their chemical structures. The highly sensitive determination of amino acids often requires derivatization. Capillary electrophoresis is a separation technique with excellent characteristics for the analysis of amino acids in biological fluids. Moreover, it offers the possibility of precapillary, on-capillary, or postcapillary derivatization. Each derivatization approach has specific demands in terms of the chemistry involved in the derivatization, which is discussed in this review. The family of homocyclic o-dicarboxaldehyde compounds, namely o-phthalaldehyde, naphthalene-2,3-dicarboxaldehyde, and anthracene-2,3-dicarboxaldehyde, are powerful derivatization reagents for the determination of amino acids and related compounds. In the presence of suitable nucleophiles they react with the primary amino group to form both fluorescent and electroactive derivatives. Moreover, the reaction rate enables all of the derivatization approaches mentioned above. This review focuses on articles that deal with using these reagents for the derivatization of amino acids and related compounds for ultraviolet-visible spectrometry, fluorescence, or electrochemical detection. Applications in capillary and microchip electrophoresis are summarized and discussed.
Keywords: Electrophoresis, Capillary; elektroforéza kapilární; On-capillary; Electrophoresis, Microchip; elektroforéza mikročipová; Stereoisomerism; stereoizomerie; Derivatization; o-Dicarboxaldehydes; Aldehydes; Precapillary; Naphthalenes; aldehydy; Postcapillary; o-ftalaldehyd; naftaleny; Amino Acids; o-Phthalaldehyde; aminokyseliny